9 Causes and mitigation strategies for mortality in neonatal and weaned piglets. (10th April 2018) - Baxter, E
Abstract: Piglet mortality continues to be a major economic and welfare concern. Despite advances in knowledge to improve piglet survival, there have been no significant improvements in practice over the last 30 years, with total mortality (i.e. stillborn and live-born deaths) per litter averaging between 16-20%. Though the multifactorial nature of piglet mortality means single causal factors are difficult to identify, the recent focus on genetic selection strategies to increase litter size, and the associated negative impacts on survival, is a likely contributing factor hindering any substantial advances. These super-prolific breeding programmes to achieve production targets of 35-40 piglets per sow per year are likely to persist. However such targets challenge both the sow and piglets, with both immediate and long-term outcomes on health, welfare and survival. The piglet faces two major transition periods in its early life; one at birth and one at weaning. Both pose significant challenges to survival. At birth the fetus transitions from an environment where it is kept warm, protected from pathogens and environmental challenges, and provided with continuous nutrition and oxygen via the umbilical cord, to a relatively hostile extra-uterine environment. This is associated with a rapid adjustment of many physiological processes to enable breathing, to develop motor functions, maintain body temperature and seek a food source (usually the maternal udder followed by sucking colostrum and milk). The transition itself can also be a risk when the birth process is prolonged or difficult so constituting a threat to the survival, with physical injury and hypoxia increasing with the duration that the piglet is in the birth canal. A viable piglet is one that will adapt to the extra-uterine environment and survive the vulnerable pre-weaning period. There are certain aspects of a piglet's physiology and behaviour which potentially aid this task including; an optimum birth weight, favourable litter size, physiologically mature organ functions maintaining homeostasis and the ability to behaviourally adapt to obtain vital nutrients from the sow. At weaning the piglet transitions from a socially stable environment with regular and synchronised feeding patterns (i.e. milk supplied and controlled by the mother) to a new environment, with new social challenges (i.e. mixing with other litters) and a complete change in the pattern and delivery of food (i.e. mainly solid, self-controlled access). Such a transition requires both behavioural and physiological adaptations and ensuring a good start in the pre-weaning period is paramount to post-weaning outcomes. The events which predispose mortality are now occurring long before the time of farrowing and need to be addressed by the increased incorporation of genetic traits favouring survival in breeding goals, nutritional interventions for the sow during gestation and lactation which enhance fetal development and neonatal vigour, and skilled stockperson assistance of low vitality and supernumerary piglets at the time of birth and colostrum intake. Such interventions will ensure pigs are not merely surviving the pre-weaning period but thriving into the post-weaning period and throughout their productive lives.